A rare presentation of benign Brenner tumor of ovary: a case report - Periasamy, Sumathi; Sengodan, Subha Sivagami; ., Devipriya; Pandian, Anbarasi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Brenner tumors are rare ovarian tumors accounting for 2-3% of all ovarian neoplasms and about 2% of these tumors are borderline (proliferating) or malignant. These tumors are commonly seen in 4th-8th decades of life with a peak in late 40s and early 50s. Benign Brenner tumors are usually small, <2cm in diameter and often detected incidentally during surgery or on pathological examination. Authors report a case of a large, calcified benign Brenner tumor in a 55-year-old postmenopausal woman who presented with complaint of abdominal pain and mass in abdomen. Imaging revealed large complex solid cystic pelvic mass -peritoneal fibrosarcoma. She underwent laparotomy which revealed huge Brenner tumor weighing 9kg arising from left uterine cornual end extending up to epigastric region. Myomectomy and hysterectomy with bilateral salphingo oophorectomy, omentectomy done and the specimen was sent for histopathological and immunohistochemistry study which revealed benign Brenner tumor. Brenner tumors are rare ovarian neoplasms accounting for 2-3% of all ovarian tumors. Benign Brenner tumors are usually small and solid whereas borderline and malignant Brenner tumors are usually larger and cystic with solid areas. But it is possible to have a completely benign large Brenner tumor. Therefore, benign nature of the lesion should not be excluded even when the ovarian tumor is very large.